2013
DOI: 10.1155/2013/798914
|View full text |Cite
|
Sign up to set email alerts
|

Common Oxytocin Receptor Gene Polymorphisms and the Risk for Preterm Birth

Abstract: Abstract.Oxytocin is crucially involved in the onset and maintenance of labor. We investigated the association between oxytocin receptor gene polymorphisms and preterm birth. The presence of four common oxytocin receptor gene polymorphisms (rs2254298, rs53576, rs2228485 and rs237911) was evaluated in one hundred women with preterm birth and one hundred healthy women using restriction fragment length polymorphism genotyping. No association was found between the presence of any individual oxytocin receptor gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…To-date many SNPs (several dozen) have been reported in the OXTR gene, however, less is known about their association with physiological processes. Recently some studies have reported association of OXTR gene polymorphisms with PTB risk [ 32 34 ]. An exhaustive study was done in 651 PTB infants and their parents for analyses of 16 single nucleotide polymorphisms (SNPs) in genes for OXT and OXTR , and leucyl/cystinyl aminopeptidase ( LNPEP ) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To-date many SNPs (several dozen) have been reported in the OXTR gene, however, less is known about their association with physiological processes. Recently some studies have reported association of OXTR gene polymorphisms with PTB risk [ 32 34 ]. An exhaustive study was done in 651 PTB infants and their parents for analyses of 16 single nucleotide polymorphisms (SNPs) in genes for OXT and OXTR , and leucyl/cystinyl aminopeptidase ( LNPEP ) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two common SNPs of OXTR (rs4686302, rs237902) were shown apparently to be associated with PTB. Kuessel et al [ 34 ] studied four common OXTR polymorphisms (rs53576, rs2254298, rs237911, rs2228485) in 100 women each with PTB and term birth. Although no relationship was revealed for each of the four individual polymorphisms and PTB, however, the haplotype combination of rs2228485 C allele, rs2254298 A allele, and rs237911 G allele was found to be significantly associated with an increased risk of PTB.…”
Section: Introductionmentioning
confidence: 99%
“…We found that in the cell model of oxidative stress, the expression level of OXTR was signi cantly increased compared with the normal cell group, which was consistent with the previous research results and proved that this gene was one of the critical reasons for the development of RSA. OXTR, an important in ammatory factor, plays a vital role in initiating and maintaining delivery (57,58). Myometrium and decidua from pregnant women who underwent cesarean section or hysterectomy during pregnancy (59), and the results showed that OXTR level was low in early pregnancy, whereas in pregnant women with at least 37-week gestational age or premature labor, OXTR level and the sensitivity to oxytocin were signi cantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…Четыре общих полиморфизма гена рецептора окситоцина (rs2254298, rs53576, rs2228485 и rs237911) были оценены у 100 женщин с преждевременными родами и 100 здоровых женщин, родивших своевременно. Было определено, что аллель rs2228485 c и аллель rs237911 G связаны с повышенным риском преждевременных родов (oR = 3,2, 95 % cI 1,04-9,8, p = 0,043) [56].…”
Section: генетические маркеры преждевременных родовunclassified